Effect of Synthetic Colloid Administration on Coagulation in Healthy Dogs and Dogs with Systemic Inflammation - Gauthier, V. (J Vet Intern Med, 2015)
BACKGROUND: Synthetic colloids are often used during fluid resuscitation and affect coagulation. OBJECTIVE: To compare the effects of an isotonic crystalloid and synthetic colloid on coagulation in healthy dogs and dogs with systemic inflammation. ANIMALS: Sixteen adult purpose‐bred Beagles. METHODS: Randomized, placebo‐controlled, blinded study. Dogs were randomized into one of two groups receiving fluid resuscitation with either 40 mL/kg IV 0.9% NaCl or tetrastarch after administration of lipopolysaccharide or an equal volume of placebo. After a 14‐day washout period, the study was repeated such that dogs received the opposite treatment (LPS or placebo) but the same resuscitation fluid. Blood samples were collected at 0, 1, 2, 4, and 24 hours for measurement of coagulation variables. RESULTS: Administration of either fluid to healthy dogs and dogs with systemic inflammation resulted in similar increases in prothrombin time and activated clotting time. In comparison to saline administration, tetrastarch administration resulted in significantly decreased R (P = .017) in healthy dogs, as well as significantly increased activated partial thromboplastin time (P ≤ .016), CL30% (P ≤ .016), and K (P < .001) and significantly decreased platelet count (P = .019), α (P ≤ .001), MA (P < .001), and von Willebrand factor antigen (P < .001) and collagen binding activity (P ≤ .003) in both healthy dogs and dogs with systemic inflammation. CONCLUSIONS AND CLINICAL IMPORTANCE: Tetrastarch bolus administration to dogs with systemic inflammation resulted in a transient hypocoagulability characterized by a prolonged activated partial thromboplastin time, decreased clot formation speed and clot strength, and acquired type 1 von Willebrand disease.